The relationship of numeracy literacy skills to self efficacy in junior high school students - Rengganis, Renti; Nuraeni, Yeyen; Aziz, Abdul (CV. Pustaka Literasi Ilmiah, 2024)
This study aims to describe the relationship between numeracy literacy skills and self-efficacy of private junior high school students in Bandung City, namely SMP Muhammadiyah 6. This study uses multivariate correlation method with a sample of 10 students with random sampling technique. The instruments used in this research are numeracy literacy test and self-efficacy questionnaire. The data were processed by descriptive and inferential quantitative methods. The results showed that students' numeracy literacy skills from the test results and questionnaire results showed no influence between the two variables. The conclusion of this study is that students who have low or high numeracy literacy skills have no influence on self-efficacy, this is based on the results of student questionnaires.